910Noise-related malfunctions in modern ICDs during oncologic radiotherapy: a multicentre, real-time, in-vitro observation. (18th June 2020) - Di Girolamo, E; Appignani, M; Marini, M; De Filippo, P; Leidi, C; Di Girolamo, F; Delana, A; Barbareschi, A; Andreoli, S; Genovesi, D; Falco, M D
Abstract: Funding Acknowledgements: None Background: Direct photon exposure of implantable cardioverter-defibrillators (ICDs) during radiotherapy is still considered not recommended, or even unsafe, by manufacturers and guidelines. The effects of photon beams on ICDs are unpredictable, depending on multiple factors, and electromagnetic interferences (EMIs) may present during exposure. Purpose: To evaluate transient ICD malfunctions by direct exposure to doses up to 10 Gy during low-energy radiotherapy, 36 contemporary wireless-enabled ICDs, with at least 4 months to elective replacement indicator (E.R.I.) were evaluated in a realtime in-vitro session. Methods: All ICDs had baseline interrogation. Single chamber devices were programmed in the VVI/40 mode and dual or triple chamber devices were programmed in the DDD/40 mode. Rate response function and antitachycardia therapies were disabled, with the ventricular tachycardia (VT)/ventricular fibrillation (VF) detection windows still working. A centering computed tomography was performed to build the corresponding treatment plan and the ICDs were blinded randomized to receive either 2, 5 or 10 Gy exposure by a low photon-energy linear accelerator (6MV) in a homemade water phantom (600 MU/min). The effective dose received by the ICDs was randomly assessed by an in-vivo dosimetry. During radiotherapy course, the devices were observed in a real-time session using manufacturer specific programmer, and ICD function (pacing, sensing, programmed parameters, detection) was recorder by the video camera in the bunker throughout the entire photon exposure. All ICDs had an interrogation session immediately after exposure. Results: During radiotherapy course, almost all ICDs (90.9%) recorded major or minor transient EMIs. On detail, 16 ICDs (44.4%) reported EMI-related atrial and/or ventricular oversensing, with base-rate-pacing inhibition and VT/VF detection. 16 ICDs (44.4%) recorded not clinically relevant minor EMIs, and no detections were observed. Only 4 ICDs (11.2%) reported neither transient malfunction nor minor EMIs, withstanding direct radiation exposure. At immediate post-exposure interrogation, the ICDs that recorded major real-time malfunctions had VT/VF detections stored in the device memory. In none of the ICDs spontaneous changes in parameter settings were reported. EMI-related malfunctions occurred regardless of either 2, 5 or 10 Gy photon beam exposure. Conclusions: Transient EMIs were observed in most of the contemporary ICDs. To avoid potentially life-threatening ICD malfunctions such as pacing inhibition or inappropriate shock delivery, magnet application on the pocket site or reprogramming in the asynchronous mode are still suggested in ICD patients ongoing even low energy radiotherapy exposure.